Long‐term evaluation of painful symptoms and fertility after surgery for large rectovaginal endometriosis nodule: a retrospective study. (20th December 2017) - Bourdel, Nicolas; Comptour, Aurélie; Bouchet, Paméla; Gremeau, Anne‐Sophie; Pouly, Jean‐Luc; Slim, Karem; Pereira, Bruno; Canis, Michel
Abstract: Introduction: Optimal surgical treatment of rectovaginal endometriosis remains a controversial topic. The objective of this study was to evaluate long‐term postoperative outcomes after rectal shaving or colorectal resection for rectovaginal endometriosis. Material and methods: 195 patients underwent surgery (172 managed by shaving, 23 by colorectal resection) between January 2000 and June 2013 for rectovaginal endometriosis (>2 cm) involving at least the serosa of the rectum. Primary outcome measures were pain and fertility. Secondary outcome measures were complications, recurrence rates and quality of life. Results: Mean follow‐up was 60 ± 42 months in the shaving group and 67 ± 47 months in the resection group. The mean VAS score for pelvic pain between the pre and postoperative period decreased from 5.5 ± 3.5 (shaving group) and 7.3 ± 2.9 (resection group) to 2.3 ± 2.4 ( p < 0.001) and 2.0 ± 1.8 ( p < 0.001), respectively. For dysmenorrhea, the mean baseline VAS score fell postoperatively from 7.7 ± 2.8 (shaving group) and 8.2 ± 2.6 (resection group) to 3.3 ± 2.9 ( p < 0.001) and 2.7 ± 2.7 ( p < 0.001), respectively. Pregnancy rates were 73% for shaving and 69% for resection. Major complications occurred in 4% of patients in the shaving group and in 26% in the resection group ( p = 0.001). Thirteen patients (7.6%) from the shaving group and none from the resection group were reoperated for suspicion of endometriosis recurrence ( p = 0.37). Postoperative quality of life scores revealed no differences between the two groups. Conclusion: Our study demonstrates that rectal shaving, when feasible for rectovaginal nodule (>2 cm) infiltrating the digestive serosa, has equal impact on pain and pregnancy rates compared with colorectal resection at long‐term follow‐up, with low complication and favorable pregnancy rates.